Dynamic efficiency of the Japanese economy - Felcánová, Kateřina; Potužák, Pavel; Kureková, Lucie; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
This thesis analyzes whether the Japanese economy was dynamically efficient or not during the years from 2003 to 2020. The concept of dynamic efficiency is explained using the overlapping generations model of Diamond (1965) and the contributions of Phelps (1961; 1965). The thesis explores the origin and implications of dynamic inefficiency as well as the possible theoretical instruments for dealing with it. Literature questioning the possibility of dynamic inefficiency is also included. Three tests are conducted to assess whether Japan is dynamically efficient or not. The first one is a preliminary test involving a comparison of the gross domestic saving rate with the capital share of output, as was suggested by Phelps (1961). This is followed by the test of Abel et al. (1989) including several corrections proposed by novel literature. An emphasis is put on precisely which aggregates are used and why. Finally, the test of Barbie et al. (2004) is performed. Contrary to previous research, the result is dynamic efficiency. A discussion about the usefulness of the tests concludes.
Vedoucí práce: Pavel Potužák
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses